Analisis Pengaruh Capital Adequacy Ratio dan Komite Audit Terhadap Profitabilitas Perusahaan Perbankan di Era Pandemi Covid-19 - Rhiesmia Sukma; Dian Imanina Burhany (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The bank's financial performance can be evaluated by profitability. In the era of the Covid-19 pandemic, especially during 2020 (March-December 2020), the profitability ratio of banks in Indonesia showed a decline. The ratio to measure the profitability of a bank is Return On Assets (ROA). ROA is important for banks because ROA is used to measure the effectiveness of the company in generating profits by utilizing its assets. Many factors affect ROA, including the Capital Adequacy Ratio (CAR) and the audit committee. To determine the effect of the Capital Adequacy Ratio (CAR) and the audit committee on the profitability of banking companies listed on the Indonesia Stock Exchange in 2020. This type of research is quantitative with a descriptive approach. The research sample uses a purposive sampling technique with the criteria of banking companies that publish Annual Reports in 2020, which are 43 banks. The data analysis method used is multiple linear regression analysis. The results of the study found that partially CAR had a positive and significant effect on ROA, but the audit committee had no significant effect on ROA. Furthermore, the CAR and the audit committee together (simultaneously) have no effect on ROA.